Cochrane Database of Systematic Reviews 2016
DOI: 10.1002/14651858.cd012021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of needle/syringe programmes and opiate substitution therapy in preventing HCV transmission among people who inject drugs

Abstract: This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the impact of needle/syringe programmes with and without opiate substitution therapy (OST) on the incidence of HCV infection among people who inject drugs (PWID).To assess the effect of OST alone on the incidence of HCV infection among PWID. Research questions How effective are needle/syringe programmes (NSP) with and without the use of OST for reducing HCV incidence among PWID? How effective is OST alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
1
37
0
1
Order By: Relevance
“…As modelling studies have shown that more frequent testing for HCV and earlier initiation of HCV treatment could reduce the HCV epidemic among HIV‐positive MSM and given that those previously infected with HCV are a particularly high risk sub‐population for transmission, reducing the time from reinfection to retreatment is important. This could be achieved by increasing the frequency of HCV reinfection screening and may require out of the box diagnostic strategies like a home‐based diagnostic approach in which the patient collects dried blot spots that are sent to the lab for HCV RNA or antigen testing. Harm reduction and other behavioural interventions to prevent infection/reinfection: Despite the importance of harm reduction such as OST and needle and syringe programs for preventing HCV infection among PWID , access to these interventions in many settings is poor, particularly in many resource limited settings . Scale‐up of harm reduction, as recommended by the WHO , is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…As modelling studies have shown that more frequent testing for HCV and earlier initiation of HCV treatment could reduce the HCV epidemic among HIV‐positive MSM and given that those previously infected with HCV are a particularly high risk sub‐population for transmission, reducing the time from reinfection to retreatment is important. This could be achieved by increasing the frequency of HCV reinfection screening and may require out of the box diagnostic strategies like a home‐based diagnostic approach in which the patient collects dried blot spots that are sent to the lab for HCV RNA or antigen testing. Harm reduction and other behavioural interventions to prevent infection/reinfection: Despite the importance of harm reduction such as OST and needle and syringe programs for preventing HCV infection among PWID , access to these interventions in many settings is poor, particularly in many resource limited settings . Scale‐up of harm reduction, as recommended by the WHO , is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…Dr. Hickman presented results from a recent Cochrane Review of 15 studies including 1089 HCV cases over 4262 person years of follow-up time. Pooled results demonstrated that exposure to OST resulted in at least a 54% risk reduction in HCV transmission [47]. Although OST and NSP have been shown to prevent HCV infections, the coverage required to achieve substantial HCV prevalence reductions may be unsustainable (80% compared to the current 50%) and therefore unlikely to be achieved [48].…”
Section: The 5th Canadian Symposium On Hcv (Cshcv)mentioning
confidence: 99%
“…Although historically viewed as being difficult to treat, PWID have been recently shown to have treatment adherence and SVR rates comparable to non-drug users (Elsherif et al, 2017) as well as a low re-infection rate (1.14 per 100 person-years)(Islam et al, 2017), indicating equally effective applicability of DAA therapy to this high-risk population. Several public health interventions (PHI) are currently available for effectively controlling HCV infections among PWID if coverage is sufficient; namely, specific DAA therapy and harm reduction programs, including syringe service programs, medication substitution treatment and peer-education interventions (PEI) (Bruggmann and Grebely, 2015; Platt et al, 2016). Although each of the interventions can contribute to reduction of incidence and prevalence of HCV infection among PWID, significant cost, complex logistics and social factors confound application of the interventions, indicating need for the development of efficient implementation strategies to eliminate hepatitis C in these communities.…”
Section: Introductionmentioning
confidence: 99%